Food Analysis - Nielsen, S. Suzanne; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This fifth edition provides information on techniques needed to analyze foods for chemical and physical properties. The book is ideal for undergraduate courses in food analysis and is also an invaluable reference to professionals in the food industry. General information chapters on regulations, labeling, sampling, and data handling provide background information for chapters on specific methods to determine chemical composition and characteristics, physical properties, and objectionable matter and constituents. Methods of analysis covered include information on the basic principles, advantages, limitations, and applications. Sections on spectroscopy and chromatography along with chapters on techniques such as immunoassays, thermal analysis, and microscopy from the perspective of their use in food analysis have been expanded. Instructors who adopt the textbook can contact the editor for access to a website with related teaching materials.
Introduction to Food Analysis -- United States Government Regulations and International Standards Related to Food Analysis -- Nutrition Labeling -- Evaluation of Analytical Data Sampling and Sample Preparation -- Basic Principles of Spectroscopy -- Ultraviolet, Visible, and Fluorescence Spectroscopy -- Infrared and Raman Spectroscopy -- Atomic Absorption Spectroscopy, Atomic Emission Spectroscopy, and Inductively Coupled Plasma-Mass Spectrometry -- Nuclear Magnetic Resonance -- Mass Spectrometry -- Basic Principles of Chromatography -- High Performance Liquid Chromatography -- Gas Chromatography -- Moisture and Total Solids Analysis -- Ash Analysis -- Fat Analysis -- Protein Analysis -- Carbohydrate Analysis -- Vitamin Analysis -- Traditional Methods for Mineral Analysis -- pH and Titratable Acidity -- Fat Characterization -- Protein Separation and Characterization Procedures -- Determination of (Total) Phenolics and Antioxidant Capacity in Food and Ingredients -- Application of Enzymes in Food Analysis -- Immunoassays -- Determination of Oxygen Demand -- Rheological Principles for Food Analysis -- Thermal Analysis -- Color Analysis -- Food Microstructure Techniques -- Analysis of Food Contaminants, Residues and Chemical Constituents of Concern -- Analysis for Extraneous Matter -- Food Forensic Investigation.
Keywords: Food science; Chemistry, Technical; Spectrum analysis